Karakter Dan Pemakaian Model Histeretik Elemen Pada Respon Inelastik Struktur beton Bertingkat Banyak - Perpustakaan UGM, i-lib ([Yogyakarta] : Fakultas Ekonomi,UGM, 1997)
In the earthquake resistant analysis and design of building structures the inelastic response of a building is allowed with several requirements. The inelastic behaviour of the reinforced concrete structure can be normally identified through the laboratory tests. Eventhough can be done, the full scale test of the building structure is very complex and expensive. The inelastic behaviour of the concrete member then is often modelled in terms of phisical, matematical and machanical models. Meanwhile the inelastic belwviour of the concrete plastic hinges is mechanically modelled as a hystereric loops. There are several flexural hysteretic models proposed by researchers. Types, load combinations and member configurations are among of parameters that will affect on the inelastic behaviour of the concrete plastic hinges. In this paper Bilinear, Clough, Modified Takeda and Q-Hyst hysteretic models have been used for simulating the flervral behaviour of the concrete platic hinges. Effects of these models on the inelastic response of the 12-storey reinforced concrete building subjected to the 1940 El Centro NSC have been investigated. Results of this investigation indicated that the Bilinear model caused the stiffest of the structure as it be compared with other models. Accordingly, the Bilinear model resulted the highest inelastic responses. The most effective hysteretic energy dissipation was developed by the Clough model and yielded the smallest structural damage indices. Modified Takeda anf Q-Hyst models caused very similar response in the most cases. Meanwhile the structural responses were significantly affected by the foundation rotations. Kala-kata Kunci : inelastik, daktilitas, daktilitas lengkung, rotasi sendi plastik, viskous energi, histeretik energi, indeks kerusakan.